Two-dimensional superhard silicon nitrides with widely tunable bandgap, high carrier mobility and hole-doping-induced robust magnetism - Ma, Shengqian; Jiang, Jiaxin; Zou, Lanlan; Lin, Jiaqi; Lu, Ning; Zhuo, Zhiwen; Wu, Xiaojun; Li, Qunxiang (Nanoscale, 2023)
The search for new forms of the traditional bulk materials to enrich their interactions and properties is an attractive subject in two-dimensional (2D) materials. In this work, novel tetra-hexa-mixed coordinated 2D silicon nitrides (Si 3 N 4 ) and their analogues are systematically investigated via density functional theory. The results show the global minimum 2D structure, Si 3 N 4 (T-aa), is a highly chemically and thermally stable superhard semiconductor with a wide indirect bandgap (about 6.0 eV), which is widely adjustable under both biaxial strain and vertical electric field. It also possesses anisotropic high carrier mobility, up to 5490 cm 2 V −1 s −1 at room temperature. Besides, its nitride analogues of group IV A (Si, Ge, Sn, and Pb) exhibit diverse electronic structures with regular bandgap distribution. Remarkably, some nitride analogues display linearly increasing robust magnetism with hole doping. The theoretical Curie temperatures of Si 3 N 4 and Sn 3 N 4 with hole doping (1h + per unit cell) are 298 and 180 K, respectively. The Si 3 N 4 (T-aa) and its analogues have a variety of excellent properties to be potentially applied in various fields, e.g. , semiconductor electronics, spintronics, high-temperature structural materials, and superhard materials. The two-dimensional (2D) new forms of ceramic material silicon nitrides and it its nitride analogues with novel properties in mechanics, electronics, and magnetics is an attractive subject in 2D materials.